1988
DOI: 10.17723/aarc.51.3.q76742568n110771
|View full text |Cite
|
Sign up to set email alerts
|

Educating the Reference Archivist

Abstract: Abstract:Although much has been written recently on archival education and the role education plays in certification and professionalization, little of this literature addresses archival reference and the skills archivists need to carry out their reference responsibilities. This inattention to the training of reference archivists reflects the field's general indifference to the reference process relative to other archival concerns. This article, through a selected survey of the literature, suggests that only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
0
8
0
6
Order By: Relevance
“…Discussions of archival core curricula include an examination of the teaching of reference, but few articles focus on the teaching of reference as a sole subject matter. Pugh's (2005) extensive bibliographic essay on reference services lists only two articles on the subject of the education of reference archivists in the past two decades- Eastwood's (1997) and Ruth's (1988) works.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussions of archival core curricula include an examination of the teaching of reference, but few articles focus on the teaching of reference as a sole subject matter. Pugh's (2005) extensive bibliographic essay on reference services lists only two articles on the subject of the education of reference archivists in the past two decades- Eastwood's (1997) and Ruth's (1988) works.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More than 20 years ago, Ruth (1988) observed that the training of reference archivists was neglected and suggested that this area be addressed through formal education so that archivists could better assist researchers in using collections. She suggested that a course on reference be undertaken early in an archivist's education, and that such a course should include user studies or a reference practicum, readings, and classroom simulations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thanks to these studies, the archival community has accumulated a great deal of important information about users. These studies address the necessity to move attention from materials to clients (Speakman 1984;Freeman 1984;Dearstyne 1987;Orbach 1991); patterns of archival users' information-seeking processes (Stevens 1977;Stieg 1981;Conway 1986b;Miller 1986;Tibbo 2003;Johnson 2002, 2003;Duff et al 2004); the importance of use and user studies (Maher 1986;Conway 1986a;Ruth 1988); researchers' citation patterns of archival materials (Elliot 1981;Beattie 1989Beattie /1990); experienced users' archival knowledge (Yakel and Torres 2003); and usability and relevancy of digital collections and finding aids in the Web environment (Tibbo 2003;Yakel 2004). These studies provide valuable understandings about archival users and form the basis of traditional user studies.…”
Section: User Studies In Archivesmentioning
confidence: 99%
“…A similar search for professional self and an associated educational evolution did not begin for archivists until the Report of the 1970s (Mason 1972 and; Society of American Archivists 1972) with most substantive curricular and programmatic development having taken place only in the past two decades. (Conway 1988;Eastwood 1988;Ruth 1988;O'Toole 1990;Ericson 1993).…”
mentioning
confidence: 99%